THE EFFECTIVENESS OF ACCOUNTING E-MODULE INTEGRATED WITH CHARACTER VALUE TO IMPROVE STUDENTS’ LEARNING OUTCOMES AND HONESTY - Destri Sambara Sitorus; Siswandari Siswandari; Kristiani Kristiani (LPMPP Universitas Negeri Yogyakarta, 2019)
This study was aimed to examine the effectiveness of e-accounting module integrated character values to improve students’ learning outcomes and honesty. This was motivated by lack of students' understanding of accounting materials so that students tended to take dishonest actions like cheating while doing assignments or examinations. Honesty is one of the characters developed in many curriculla, so that honest character needs to be integrated in learning activities. The data collected in this study were the data on students’ learning outcomes collected through multiple choice tests and the data on students’ honesty collected through questionnaires. Students’ learning outcomes data were analyzed through independent sample t test and the data on students' honesty were analyzed descriptively by narrative. The t test results obtained sig values 0.014 0.05 so that there were significant differences between the learning outcomes of the experimental class and the control class. The results of the questionnaire analysis showed that the students’ honesty level of the experimental class was in a very good category and the control class was in the good category.